An interface of wireless network traffic analysis [electronic resource] - 221487 Ahmad Mohamed Jamil Mohamed Almoustafa; Muhammad Shafie Abd. Latif, supervisor (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2007